Psychophysiological Associations between Chronic Tinnitus and Sleep: A Cross Validation of Tinnitus and Insomnia Questionnaires. (25th October 2015) - Schecklmann, Martin; Pregler, Maximilian; Kreuzer, Peter M.; Poeppl, Timm B.; Lehner, Astrid; Crönlein, Tatjana; Wetter, Thomas C.; Frank, Elmar; Landgrebe, Michael; Langguth, Berthold
Abstract : Background . The aim of the present study was to assess the prevalence of insomnia in chronic tinnitus and the association of tinnitus distress and sleep disturbance. Methods . We retrospectively analysed data of 182 patients with chronic tinnitus who completed the Tinnitus Questionnaire (TQ) and the Regensburg Insomnia Scale (RIS). Descriptive comparisons with the validation sample of the RIS including exclusively patients with primary/psychophysiological insomnia, correlation analyses of the RIS with TQ scales, and principal component analyses (PCA) in the tinnitus sample were performed. TQ total score was corrected for the TQ sleep items. Results . Prevalence of insomnia was high in tinnitus patients (76%) and tinnitus distress correlated with sleep disturbance (r = 0.558 ). TQ sleep subscore correlated with the RIS sum score (r = 0.690 ). PCA with all TQ and RIS items showed one sleep factor consisting of all RIS and the TQ sleep items. PCA with only TQ sleep and RIS items showed sleep- and tinnitus-specific factors. The sleep factors (only RIS items) were sleep depth and fearful focusing. The TQ sleep items represented tinnitus-related sleep problems. Discussion . Chronic tinnitus and primary insomnia are highly related and might share similar psychological and neurophysiological mechanisms leading to impaired sleep quality.